Factors Contributing to Resistance Toward Alternative Assessment Models Among Faculty - Ebrahimpour, Delaram (Assessment and Practice in Educational Sciences, 2023)
This study aims to explore the key individual, institutional, and cultural factors that contribute to faculty resistance toward the implementation of alternative assessment models in higher education. This qualitative study employed a descriptive research design using semi-structured interviews to gain insights into faculty perspectives on assessment innovation. A purposive sample of 27 faculty members from universities in Tehran, Iran, participated in in-depth interviews. Data collection continued until theoretical saturation was achieved. Interviews were transcribed and analyzed thematically using Nvivo 12 software. Thematic analysis followed Braun and Clarke’s framework, and the credibility of findings was supported through participant validation and peer debriefing. The analysis revealed three overarching themes: individual-level barriers, institutional and structural constraints, and cultural and normative resistance. Within the first theme, faculty reported lack of familiarity with alternative models, perceived complexity, fear of losing authority, low self-efficacy, and concerns about workload. The second theme highlighted structural impediments such as unclear institutional policies, limited resources, inadequate professional development, and misaligned promotion criteria. The third theme emphasized cultural influences, including adherence to traditional academic identity, peer pressure, student expectations, and skepticism about assessment validity. These findings underscore that resistance is multifaceted and contextually embedded rather than rooted in mere unwillingness. Resistance to alternative assessment models among faculty is shaped by a complex combination of psychological, institutional, and cultural factors. Addressing these barriers requires an integrated approach involving professional development, supportive policy reforms, incentive structures, and cultural change at the departmental and institutional levels. Without systemic alignment and stakeholder engagement, efforts to implement assessment reform are likely to remain limited in scope and sustainability.